An investigation of the failure mechanisms of lead anodes in copper electrowinning cells. (January 2020) - Elrefaey, A.; Gu, Y.; James, J.D.; Kneen, C.; Crabbe, I.; Sienz, J.
Highlights: The electrochemical performance of lead anodes relies on the protective ability of PbO2. Lead anodes sometimes failed under unusually short periods of service. Manganese ions are electrochemically active at lead alloy anodes. Manganese causes the failure of anodes in spite of the short service time. Methods were suggested to overcome the manganese problem in tankhouse. Abstract: Lead alloys are used as permanent anodes for electrowinning of base metals such as copper. The corrosion of anodes is costly because of their relatively short lifetime, material cost, and their impact on cathodic deposit quality. Failure of anodes sometimes occurs before the predicted lifetime, having a negative impact on the efficiency and economics of the electrowinning process. This study investigates some recently failed lead alloy anodes. These failures occurred after a short period of service in a commercially operating electrowinning tank house. The samples were metallographically investigated with the help of an optical, three-dimensional microscope and a scanning electron microscope (SEM) equipped with Energy-Dispersive X-ray Spectroscopy (EDS) analysis. It is suggested that the reasons for failure are improper operational issues in the tank house, especially the level of manganese content in the electrolyte, which leads to unexpected corrosion.